Varstvo blagajevega volčina (Daphne blagayana Freyer) v gozdnogospodarskem območju Ljubljana - Omejc, Jana (Zbornik gozdarstva in lesarstva, 2005)
The Blagay Daphne (Daphne blagayana Freyer) was one of the first legally protected plants in Slovenia. As the species occurs mostly in forest habitats,we attempted to determine its present condition and the extent to which protection principles are considered and practiced in the Ljubljana forest-management region, where the plant was discovered. The analysis of ninehabitats showed that despite the legal protection of Blagay Daphne in Slovenia, little is known about its distribution, and that many of the habitats it occurs in are unregistered and practically unknown. Three unrecorded habitats were found during the research in the quadrant of the Central European floristic mapping scheme 9852/3. Insufficient knowledge of its range and ignorance of the prescribed guidelines regarding the protection of protected and threatened species are the main reasons for this species becoming increasingly endangered.
Keywords: Blagajev volčin; Daphne blagayana Freyer; ogrožene vrste; Slovenia; Slovenija; varstvo rastlin